Changes in Anti-nutritional Factors and Functional Properties of Extruded Composite Flour - Duguma, Haile Tesfaye; Forsido, Sirawdink Fikreyesus; Belachew, Tefera; Hensel, Oliver (Frontiers in Sustainable Food Systems, 2021)
Background: Development of complementary foods by mixing plant based (cereals, pulses and oilseeds and other) ingredients and employing various processing techniques is widely reported. Information on the effect of extrusion cooking on quality of complementary foods made from multi mixes is limited. In this regard, the objective of this study was to investigate the influence of extrusion cooking on anti-nutritional and functional properties of a newly developed extruded oats, soybean, linseed and premix composite complementary food flour. Methods: Thirteen different blending ratios of oats, soybean, linseed and premix were generated using a constrained D-optimal design of experiment. Each of the 13 blends was divided into two groups; half was extruded, and half was not. Anti-nutritional and functional properties were determined using standard methods for both extruded and unextruded composite flour. ANOVA was used to determine if there are significant differences within the group and paired t-tests were used to check variation between groups. Results: The result has shown that phytate content of the extruded and unextruded composite flour were 158.93-191.33mg/100g and 175.06-203.10mg/100g, respectively. Whereas tannin content of the extruded and unextruded composite flour were 8.4-22.89mg/100g and 23.67-36.97mg/100g, respectively. ANOVA showed phytate and condensed tannin content of the extruded composite flour was a significant difference. Water absorption capacity and bulk density showed a significant (P<0.05) difference for both extruded and unextruded. Paired t-test indicated that there is a significant (P<0.05) difference between extruded and unextruded composite flours in terms of phytate and tannin. Phytate, tannin and water absorption capacity of composite flour were increased as the proportion of soybean and linseed flour increased. However, bulk density was increased with an increasing proportion of oat in the blend. Conclusion: The findings revealed that extrusion cooking significantly reduced phytate and condensed tannin content and improved the functional properties of the composite complementary food flour. Further investigation is needed on other anti-nutritional factors which are not included in this research.